Occult moisture inputs in the fynbos : Foliar moisure uptake in Ericaceae, Restionaceae and Proteaceae / Annabelle J. Rogers - Rogers, Annabelle J (Department of Biological Sciences, 2015)
'Occult' precipitation may be an important moisture source that can impact specific plant responses to water stress in certain ecosystems. Species in many ecosystems have been shown to use this moisture source via foliar moisture uptake. The Cape Peninsula and the surrounding southern coast experience high altitude mountain cloud cover in the summer dry period. Previous work on species that exist exclusively in the cloud belt found that species from the Erica and Restionaceae family were able to absorb water through their leaf surfaces, while members of the Proteaceae were unable to do so (Gibson, 2012). Adding to the body of research, this study explores whether foliar uptake occurs in species that do not exist in the cloud belt of the Cape Peninsula and the relative importance of this method of uptake in positively impacting a plants water balance during a cloud event. Direct foliar uptake was assessed at the leaf level using two methods; submersion and mist exposure. The importance of foliar uptake was measured at the whole plant level by exposing whole plants to cloud in a mist chamber. By covering the soil in a subset of plants, we were able to isolate the importance of foliar uptake relative to uptake via drip. Results found that the restios and ericas showed a stronger ability to take up moisture via their leaves than protea species, which showed little ability to do so. In contrast to this, the mist exposure method showed no significant uptake in any species except E. quadrangularis. This disparity is possibly due to specific leaf morphology. All species showed significant hydration in response to a whole plant cloud event in both the covered and uncovered treatments. The significant hydration in response to an occult event suggests that certain low land species are capable of utilizing small occult inputs despite the lack of regular summer cloud events as seen in the cloud belt species. As family patterns of foliar moisture uptake seen in cloud belt species (Gibson 2012) are conserved in the surveyed low land species, it can be concluded that moisture uptake is not a trait specific to cloud belt species, and represents a family level pattern of ability.